Career Management and Job Satisfaction among Female Uniformed Personnel of Philippine National Police - Acorda, Emmalyn; Agmata, Jeffrey; Napadao, Mary Jane; Perilla, Sesinando; Buena-Villa, Elizabeth; Villarta, Jose Andres; Tayobong, Almerian (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The aimed of this study was to ascertain how female uniformed Philippine National Police members manage their careers and how satisfied they are with their jobs. This study used survey methods in conjunction with descriptive correlation analysis. The San Juan City Police Station was the only location used for research with twenty-five (25) female uniformed personnel in the research area served as the respondents. Martinez (2019) provided a survey questionnaire that was used as the research instrument in this study. They used the mean and Pearson-r Correlation to examine the data. According to the survey, female officers support the program's implementation and are usually satisfied with its goals. Although they are contented with their compensation and benefits, they nevertheless require additional fundings in order to carry out their duties as professionals. Work satisfaction among female officers is effectively increased by the career management and development program, as evidenced by promoting gender equality and creating inclusive work environment. Investing in professional development boosts female officers' morale, motivation, and commitment to their jobs. Higher retention rates follow from this, particularly for law enforcement agencies. Additionally, the program improves performance and productivity, which helps the Philippine National Police succeed overall.